Opportunities to prevent fatalities due to injury: a cross‐sectional comparison of prehospital and in‐hospital fatal injury deaths in New Zealand. (1st February 2021) - Lilley, Rebbecca; Kool, Bridget; Davie, Gabrielle; de Graaf, Brandon; Dicker, Bridget
Abstract: Objective : There is interest in opportunities that lie in the prehospital setting to reduce the substantial burden of fatal injury. This study examines the epidemiology of prehospital and in‐hospital fatal injury in New Zealand. Methods : All deaths registered in 2008–2012 with an underlying cause of death external cause‐code V01‐Y36 (ICD‐10‐AM) were identified. The setting of death was determined following linkage to, and review of, hospital discharge data and Coronial records. Results : Of 7, 522 injury deaths, 80% occurred in a prehospital setting, with the highest burden relating to males. Within those fatally injured, 25–54‐year‐olds had a higher risk of prehospital death than 55–84‐year‐olds (adjusted Relative Risk [aRR] 1.20, 95%CI 1.16, 1.20). Similarly, those injured due to drowning (aRR 1.39, CI 1.26, 1.53) and non‐hanging suffocation (aRR 1.31, CI 1.18, 1.45) had a higher risk of prehospital death than those 'struck by/machinery'. Conclusion : Prehospital deaths account for four out of five fatal injuries in New Zealand. Of the fatally injured population, the probability of prehospital death differed by age, sex, injury mechanism and intent. Implications for public health : This study highlights the importance of strengthening prevention efforts to reduce the substantive burden of prehospital fatalities in New Zealand.